CONTENT MARKETING, PRODUCT QUALITY, AND ENGAGEMENT TOWARD PURCHASE INTENTION: THE MODERATING ROLE OF BRAND IMAGE IN GEN Z TIKTOK USERS - Komang Bagus Bre Sanjaya Aryaputra; Luh Putu Mahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates the effects of content marketing, product quality perception, and customer engagement on purchase intention, with brand image as a moderating variable, in the context of Gen Z TikTok users of Amertha Fishing Tackle Shop. Using a quantitative approach, data were collected from 210 respondents via online questionnaires and analyzed through SEM-PLS using SmartPLS. Findings revealed that all three independent variables positively and significantly influence purchase intention. Brand image was found to strengthen the effect of product quality and customer engagement, but not content marketing. These results contribute to the understanding of digital consumer behavior and marketing strategy optimization.